Cost management in technological processes taking into account the implementation of the resource saving policy - A. I. Shinkevich; O. V. Antipova (Вестник университета, 2021)
The most important factor in maintaining the positions of Russian oil companies at the global level is taking into account the factors of changes in the external environment and the activation of internal reserves. The development of effective management decision support systems requires new management concepts based on current advances in production management theory and practice. The article proposes an approach based on determining the optimal combination of resources used in the production process and assessing their impact on the formation of production costs. The concept of cost management is based on an analysis, included the specifics of the enterprise’s internal environment and an assessment of the external environment impact on it. A cost management methodology has been developed to reduce the labour intensity of decision-making and the likelihood of technical selection errors, and to increase the efficiency of resource use and cost management. The proposed approach to cost management model formation has been recommended for using at oil industry enterprises. It can also be applied to enterprises in other industries by developing key performance indicators that affect the main cost items of the technological process under consideration.